Man and woman myths and stereotypes - Susch, Eric; The Center for Humanities (Australia : The Center for Humanities, 1985)
This program examine how literature, art, movies, media and music perpetuate artificial male and female roles
Title from title screen
Video camera, Matthew Howe
DVD Format
NTSC/PAL
Keywords: Sex differences; Sex role; Stereotypes (Social psychology); Man-woman relationship